Analysis of Scientific Literacy in Class IX Middle School Students of Rantau Utara Regency in Science Learning - Ningsih, Tri Suryani; Chastanti, Ika (Universitas Labuhanbatu, 2023)
Science literacy is a very important thing for students where with scientific literacy students can have an ability in writing and reading, as well as knowing the things they learn and can give conclusions in a lesson learned and can explain the phenomena around in this case science literacy is very important for everyone, This study aims to be able to know and see how Science Literacy Abilities in Class XI Students in Science Learning at North Rantau Junior High School, Labuhanbatu Regency, The method in the research used is descriptive qualitative. The sample in this study was 30 students and 4 teachers at North Rantau Junior High School, Labuhanbatu Regency. The data collection technique was carried out by giving questionnaires, observations and interviews. The results in the study showed that on the indicators of science literacy in class IX students of North Rantau Junior High School in science learning, namely 1). Insight Knowledge of science literacy obtained a value of 65.23% 2.) Implementation of the Science Literacy Process obtained a value of 53.99% 3.) Attitude in science literacy obtained a value of 61.24% 4.) Understanding and motivation in science literacy obtained a value of 42.15%.in this case that science literacy greatly supports learning for students and can improve student learning outcomes